Caregiver perspective on pediatric attention-deficit/hyperactivity disorder: medication satisfaction and symptom control - Fridman, Moshe; Banaschewski, Tobias (Neuropsychiatric disease and treatment, 2017)
Caregiver perspective on pediatric attention-deficit/hyperactivity disorder: medication satisfaction and symptom control Moshe Fridman,1 Tobias Banaschewski,2 Vanja Sikirica,3 Javier Quintero,4 M Haim Erder,3 Kristina S Chen5 1AMF Consulting, Inc., Los Angeles, CA, USA; 2Department of Child and Adolescent Psychiatry and Psychotherapy, Central Institute of Mental Health, Medical Faculty Mannheim of the University of Heidelberg, Mannheim, Germany; 3Global Health Economics Outcomes Research and Epidemiology, Shire, Wayne, PA, USA; 4Psychiatry Department, Hospital Universitario Infanta Leonor, Complutense University, Madrid, Spain; 5Global Health Economics Outcomes Research and Epidemiology, Shire, Lexington, MA, USA Abstract: The caregiver perspective on pediatric attention-deficit/hyperactivity disorder (ADHD) study (CAPPA) was a web-based, cross-sectional survey of caregivers of children and adolescents (6–17 years of age) with ADHD and was conducted in 10 European countries. CAPPA included caregiver assessments of global medication satisfaction, global symptom control, and satisfaction with ADHD medication attributes. Overall, 2,326 caregiver responses indicated that their child or adolescent was currently receiving ADHD medication and completed the “off medication” assessment required for inclusion in the present analyses. Responses to the single-item global medication satisfaction question indicated that 88% were satisfied (moderately satisfied to very satisfied) with current medication and 18% were “very satisfied” on the single-item question. Responses to the single-item global symptom control question indicated that 47% and 19% of caregivers considered their child or adolescent’s symptoms to be “controlled” or “very well controlled”, respectively. Significant variations in response to the questions of medication satisfaction and symptom control were observed between countries. The correlation between the global medication satisfaction and global symptom control questions was 0.677 (P<0.001). Global medication satisfaction was significantly correlated (P<0.001) with all assessed medication attributes, with the highest correlations observed for symptom control (r=0.601) and effect duration (r=0.449). Correlations of medication attributes with global symptom control were generally lower than with global medication satisfaction but were all statistically significant (P<0.001). CAPPA medication satisfaction and symptom control were also significantly correlated (P<0.001) with symptom control as based on the ADHD-Rating Scale-IV symptom score and the number of bad days per month when on medication. In conclusion, caregiver responses in this European sample suggest that current treatment could potentially be improved. The observed correlations of global medication satisfaction with global symptom control and other CAPPA assessments, including medication attributes, provide support for the inter-connectivity of the medication satisfaction and symptom control. Keywords: ADHD, CAPPA, child/adolescent, Europe, medication attributes